Experimental study on properties of liquefied stabilized soil produced with different types of solidifiers and thickeners - Yuji Shigematsu; Shinya Inazumi; Ryo Hashimoto; Hiromoto Yamauchi (Case Studies in Construction Materials, 2023)
Liquefied soil stabilization methods have been applied in a wide range of construction projects especially in Japan for the effective geotechnical reuse of construction-generated soil. However, after the placement of the liquefied stabilized soil is complete, water often rises to the surface and causes the bleeding phenomenon. Chromium oxide, which is produced in the manufacturing process of iron ore and steel scrap, is sometimes added to the cement solidifier (OPC solidifier) that is mixed into the liquefied stabilized soil. The environmental conditions under which the cement solidifier and construction-generated soil encounter each other change the transformation of the chromium oxides, i.e., they leach as hexavalent chromium. Hexavalent chromium is more likely to be leached when the pH is low or the moisture content is high. These are some of the environmental issues related to the application of liquefied stabilized soil. In this study, the addition of a thickener for liquefied stabilized soil is proposed; it is used to prevent segregation while maintaining fluidity. Specifically, the authors conduct various laboratory experiments, and then perform several physical analyses using the specimens after the experiments to investigate how the addition of the thickener has changed the properties of the liquefied stabilized soil. The authors also examine the properties of each type of liquefied stabilized soil by comparing it to normal liquefied stabilized soil when the amount of OPC solidifier in the liquefied stabilized soil is reduced, and instead, a solidifier mixing with waste glass powder and blast furnace slag is used to make the liquefied stabilized soil.